Molecular and cellular mechanisms of engram allocation and maintenance - Gülmez Karaca, Kübra; Kupke, Janina; Oliveira, Ana (Brain research bulletin, 2021)
Understanding how we learn and remember has been a long-standing question in neuroscience. Technological developments of the past 15 years have allowed for dramatically increased access to the neurons that hold the physical representation of memory, also known as a memory trace or engram. Such developments have tremendously facilitated advancement of the memory field, since they made possible interrogation of the cellular and molecular mechanisms underlying memory formation with unprecedented cellular specificity. Here, we discuss the studies that have investigated rules governing neuronal recruitment to a particular memory engram. Furthermore, we provide an overview of the evidence that functional and structural changes associated with memory consolidation occur in engram neurons. Moreover, we summarize the expanding literature showing that transcriptional regulatory factors such as transcription factors and epigenetic mechanisms play an important role in the maintained allocation of behaviorally-selected neurons to an engram. Together, these studies have begun elucidating how neuronal networks are selected and modified in order to support memory formation and storage.
Gesehen am 28.07.2021